PENGARUH IMPLEMENTASI MANAJEMEN KELAS TERHADAP PERILAKU BELAJAR MAHASISWA PADA JURUSAN MANAJEMEN PENDIDIKAN ISLAM FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Ahmad Afiif; Ridwan Idris (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
This paper contains the results of the research which aimed to determine the ef-fect of the implementation of classroom management on students learning beha-vior at the Department of Islamic Education Management at Tarbiyah and Tea-ching Faculty of UIN Alauddin Makassar. The research approach was quantita-tive with the type of Ex Post Facto and the model of research was descriptive cor-relational study. The population of the research was all of the students of the De-partment of Islamic Education Management of Tarbiyah and Teaching Faculty. The sample consisted of 31 students. The methods that were used in the data col-lection was a questionnaire on the implementation of classroom management and a scale of learning behavior. Data analysis techniques used was simple linear reg-ression formula. The results of the research pointed-out that there was a positive correlation between the implementation of classroom management and students learning behavior. This means that the better the implementation of class mana-gement, the better the student learning behavior.